Clinical significance and prognostic relevance of KRAS, BRAF, PI3K and TP53 genetic mutation analysis for resectable and unresectable colorectal liver metastases: A systematic review of the current evidence. (June 2018) - Tsilimigras, Diamantis I.; Ntanasis-Stathopoulos, Ioannis; Bagante, Fabio; Moris, Demetrios; Cloyd, Jordan; Spartalis, Eleftherios; Pawlik, Timothy M.
Abstract: Background: Hepatic resection is considered the optimal potentially curative treatment for colorectal liver metastases (CRLM). Following resection, up to two-thirds of patients will develop recurrence within 5-years. Genetic mutation analysis of CRLM, especially KRAS status, has been proposed as a means to guide treatment, as well as identifying patients who can derive the most survival benefit from hepatic resection. Methods: A systematic review of the literature was conducted the PubMed, Embase and Cochrane library through February 8th, 2018. The following algorithm was applied: "(colorectal OR rectal OR colon OR colonic) AND (liver OR hepatic) AND (metastasis OR metastases) AND (gene OR mutation OR KRAS OR BRAF OR SMAD4 OR RAS OR TP53 OR P53 OR APC OR PI3K OR MSI OR EGFR OR MACC1 OR microsatellite)." Results: From the 2404 records retrieved, 78 studies were finally deemed eligible; 47 studies reported mutational data on patients with resectable CRLM, whereas 31 studies reported on patients with unresectable CRLM. Mutational analyses were mostly performed on the CRLM specimen rather than the primary CRC. The vast majority of studies reported on the KRAS mutational status (88.5%, n = 69/78). Prevalence of KRAS mutations ranged from 25% to 52%. Most studies reported that RAS mutation was a negative prognostic factor for overall (OS) (n = 24) and recurrence-free (RFS) (n = 9) survival; a few reports noted no effect of RAS mutational status on OS (n = 4) or RFS (n = 6). Twelve studies reported on BRAF mutations with a prevalence of BRAF mutation ranging from 0 to 9.1% in resected CRLM specimens. BRAF mutation was strongly associated with a worse prognosis. TP53 and PIK3CA gene mutations did not affect long-term outcomes. Conclusions: The biological status of each tumor provides the basis for individualized cancer therapeutics. Data on the mutational status on CRLM should be a part of multidisciplinary discussions to help inform the therapeutic approach, type of chemotherapy, as well as timing and approach of surgical resection. Highlights: Prevalence of KRAS mutations in CRLM specimen ranges from 25% to 52%. RAS mutation is a negative prognostic factor for OS and RFS. Prevalence of BRAF mutations ranges from 0 to 9.1% in resected CRLM specimens. BRAF mutation is strongly associated with a worse prognosis. TP53 and PIK3CA gene mutations do not seem to affect long-term outcomes.